Status Sosial Ekonomi Orang Tua Terhadap Karies Gigi dan Mulut Anak Di SD Islam Paropo Kota Makassar - Asridiana, Asridiana; Thioritz, Ernie; Yunita Arifin, Sarti (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Socioeconomic status is a person's particular position relative to other people in a group or class of society. Increasing socio-economic status is a risk factor for dental caries and is generally measured from indicators such as income, education level, lifestyle and dental health behavior. The aim of this research was to determine the socio-economic status of parents and the dental and oral caries status of children at Paropo Islamic Elementary School in Makassar City by looking at parents' income, education and employment. The method used in this research is total sampling with bivariate analysis using a correlation test by looking at socio-economic status, which is classified based on the income, education and employment of parents. The study utilized a sample of 84 students from Paropo Islamic Elementary School in Makassar City.. The results obtained from this study showed that children at Paropo Islamic Elementary School had a high frequency of caries as many as 52 students (61.90%). For the results of parents' socio-economic calculations seen from parents' income using the Mann-Whitney correlation calculation, it shows p value = 0.841, and for parents' occupation it shows p value = 1,000, while for parents' education it shows p value = 0.943. Based on this research, it can be concluded that there is no relationship between socio-economic status and the dental caries status of children at Paropo Islamic Elementary School, Makassar City. Keywords: Social; economy; dental caries